2017
DOI: 10.1097/shk.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

Burn Serum Stimulates Myoblast Cell Death Associated with IL-6-Induced Mitochondrial Fragmentation

Abstract: Background: Burn patients suffer muscle mass loss associated with hyperinflammation and hypercatabolism. The mitochondria are affected by this metabolic alteration. Mitochondrial fission activates a caspase cascade that ultimately leads to cell death. We postulate that burn-induced muscle loss is associated with increased mitochondrial fission and subsequent functional impairment. Further, we investigated whether the cytokine IL-6 plays a major role in mitochondrial fission-associated cell death after burn. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
(42 reference statements)
4
12
0
Order By: Relevance
“…Moreover, the previous study also implicated cardiac apoptosis and inflammation, which has also shown to be time dependent (9,10). As one of the cytokines implicated in the acute inflammatory response to burn, IL-6 has also been shown to induce mitochondrial fragmentation of myoblasts in vitro (41) and may contribute to mitochondrial dysfunction in this model. Additionally, although hyperglycemia has been shown to induce cardiac mitochondrial damage in other burn models (49), we did not see any difference in circulating glucose levels in the two groups (data not shown).…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, the previous study also implicated cardiac apoptosis and inflammation, which has also shown to be time dependent (9,10). As one of the cytokines implicated in the acute inflammatory response to burn, IL-6 has also been shown to induce mitochondrial fragmentation of myoblasts in vitro (41) and may contribute to mitochondrial dysfunction in this model. Additionally, although hyperglycemia has been shown to induce cardiac mitochondrial damage in other burn models (49), we did not see any difference in circulating glucose levels in the two groups (data not shown).…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, previous studies have proposed skeletal muscle cell apoptosis was increased following burn and involved in classical caspase-dependent pathways [19][20][21][22][23]. As Yasuhara et al reported increased apoptosis and caspase-3 activity in skeletal muscle within a few hours after burn in a rat model [20].…”
Section: Ivyspringmentioning
confidence: 95%
“…The pathways by which IL-6 might act in the nervous system are not completely understood yet. 2 , 16 , 19 , 51 , 98 Interestingly, some very recent studies show that upon brain injury, a reduction of IL-6 prevented neuronal cell death, therefore suggesting a clear link between IL-6 and neurodegeneration. 2 , 19 …”
Section: Low-density Lipoprotein Receptor-related Protein 1 In Neurodegeneration and Painmentioning
confidence: 99%